Decoding the role of tannic acid in wound healing: a dual‐action mechanism linking IL‐1β modulation and FGF‐driven tissue repair - Swastini, Dewa Ayu; Nugroho, Agung Endro; Martien, Ronny; Fachiroh, Jajah; Khafi, Muhammad; Putra, Komang Dian Aditya (Indonesian Journal of Biotechnology, 2026)
Tannic acid (TA) has been shown in a previous study to expedite cutaneous wound healing in rats; however, the precise mechanism by which it operates remains poorly understood. This research evaluates the effects of TA on wound healing using both in vitro and in silico methods. In vitro, its influence on the inflammatory cytokine interleukin‐1β (IL‐1β) and the growth factor fibroblast growth factor (FGF) throughout the healing process were assessed. In silico molecular docking was employed to predict direct ligand–protein interactions and to provide a mechanistic insight into whether these proteins represent primary molecular targets or downstream effects. Parameters evaluated included cell viability and proliferation, scratch assays, and the activity of pro‐inflammatory cytokines in the lipopolysaccharide (LPS)‐stimulated RAW 264.7 macrophage cell line, together with growth factors in the NIH 3T3 fibroblast cell line; all were evaluated using enzyme‐linked immunosorbent assay (ELISA). The results indicate that TA significantly facilitates wound closure by promoting NIH 3T3 fibroblast cell proliferation, enhancing FGF expression, and suppressing IL‐1ß synthesis in both in vitro and in silico approaches. These findings suggest that TA may hold considerable promise for wound‐healing management.